BIOLOGICAL CELL AND MOLECULAR COMMUNICATION TECHNOLOGY: OVERVIEW AND CHALLENGES - Farhan, Farhan; Mushfiq, Merab (European Scientific Journal, ESJ, 2015)
This paper outlines the study and overview of molecular and cell communication technology. It provides cell communication as a new paradigm in reference with engineering and communication mechanisms. Unlike current telecommunication paradigm, cell communication uses molecules as carriers of information. This study summarizes the features, characteristics and architecture of molecular communication.